Usaha Kedai Kopi Berbasis Modal Sosial - Fitri Sekti Indriani; Yuhastina Yuhastina; Yosafat Hermawan Trinugraha (Mahesa Research Center, 2022)
This study tested the social capital consept of Robert D. Putnam encompassing the essential components such as a networking, the norm of reciprocity and trust in the coffee shop of economic actors. An important problem in this study is how the role of external actors as social capital in the running of the Yu Bunt Coffee Shop business is. This study is a qualitative study with a case study approach to the coffee shop business. The data in this study were obtained through the method of involved observation, in-depth interviews, and documentation. The results of the study show that the social capital of each individual involved forms a network that is able to produce reciprocal norms, and trust which also affects the sustainability of the Yu Bunt Coffee Shop business. Meanwhile, the role of external actors in the form of friendship greatly affects the level of income and business success of the Yu Bunt Coffee Shop. The contribution of this study is social capital related to the role of external actors is an important aspect that must be maintained for the survival and success of small businesses such as coffee shops in this case study. This is important because there is a reciprocal principle that operates intersubjectively in the social capital network that is formed.